2022
DOI: 10.1002/ajh.26691
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of functional SARS‐COV‐2‐specific immunity from donor graft to hematopoietic stem cell transplant recipients

Abstract: Immunocompromised recipients of allogeneic hematopoietic stem cell transplant (HCT) are at increased risk of severe COVID-19. 1 During the first year of a successful HCT, circulating T-cells arise from donor CD34 + cells and can react to antigens exposed to the donor through natural infection or vaccination before transplantation. Therefore, donor pathogen exposure or vaccination pre-graft can be beneficial to the recipient when mounting cellular and humoral response to augment immune reconstitution and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Hence, the robust levels of CMV‐specific T cells observed at day +28 during the engraftment period were likely expanded in the donor by Triplex vaccination and transferred with the stem cell graft in the recipients. The concomitant finding of significantly enhanced levels of MVA viral vector‐specific T cells at day +28 in Triplex vaccinated MRD recipients, compared to unvaccinated MRD recipients further supports that T cells, induced in donors by Triplex vaccination could be transferred into the recipients at infusion 29,42 . Studies on durability of immunity after smallpox vaccination showed that vaccinia‐specific antibodies may persist up to 75 years post‐vaccination, whereas T‐cell responses have a half‐life of 8–15 years 55 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Hence, the robust levels of CMV‐specific T cells observed at day +28 during the engraftment period were likely expanded in the donor by Triplex vaccination and transferred with the stem cell graft in the recipients. The concomitant finding of significantly enhanced levels of MVA viral vector‐specific T cells at day +28 in Triplex vaccinated MRD recipients, compared to unvaccinated MRD recipients further supports that T cells, induced in donors by Triplex vaccination could be transferred into the recipients at infusion 29,42 . Studies on durability of immunity after smallpox vaccination showed that vaccinia‐specific antibodies may persist up to 75 years post‐vaccination, whereas T‐cell responses have a half‐life of 8–15 years 55 .…”
Section: Discussionmentioning
confidence: 61%
“…Emphasis is usually placed on post‐transplant vaccination, but there are data on the efficacy of pretransplant vaccinations, and trials have shown promising results if both recipients and donors receive vaccinations before transplantation 40,41 . Recent evidence supports that immunization of donors and recipients before HCT can significantly enhance immunogenic T and B cell responses and increase response to vaccination post‐HCT 29,42 . However, there is limited availability of long‐term safety data on using vaccination in donors and recommendation for donor vaccination still faces logistical and ethical challenges 43–45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Jullien et al (122), with a higher humoral response in the vaccinated-donor group (representing 9 of 17 patients studied). In their study, La Rosa et al (123), reported the transfer of passive cellular and humoral immunity from the donor to the recipient. After a selection of three vaccinated donors (with two of them who probably had asymptomatic COVID-19 based on the presence of anti-N antibodies), they analyzed the transfer of immunity in three recipients, one of whom was not vaccinated prior to transplant.…”
Section: Impact Of Donor Vaccinationmentioning
confidence: 99%
“…It has been shown by us and others that donor B-and T-cell immunity from pathogen exposure or vaccination pre-graft collection can be transferred to the recipient, expanding during immune reconstitution and improving vaccination responses and/ or controlling post-HCT infections (16,17). In recipients with a successful HCT outcome, circulating T cells arise from donor CD34 + cells during the first year post-HCT and can react to antigens exposed to the donor through natural infection or vaccination before transplantation (18,19).…”
Section: Introductionmentioning
confidence: 99%